PENGGUNAAN MEDIA ELEKTRONIK DALAM PEMBELAJARAN DARING IPA UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Novella, Olvin; Erman, Erman (PENSA E-JURNAL: PENDIDIKAN SAINS, 2023)
This research aimed to determine the improvement of student learning outcomes through online learning electronic media. This was a pre-experimental with one group pretest-posttest design. Data collected using written tests and response questionnaires. The learning outcomes data were analyzed using the Wilcoxon test and calculated the N-Gain score. The results of this study, namely: (1) there was an increase in student learning outcomes as evidenced by the average N-Gain score on high criteria; (2) Wilcoxon Signed Ranks test results show a significant difference between pretest and posttest results. Based on the results obtained, it can be concluded that the implementation of the science learning electronic media (E-PIPA) can improve student learning outcomes.